Optimization and Validation of in vitro Proliferation of Rat’s Peripheral Blood Mononuclear Cells (PBMNCs) Stimulated with Phytohemagglutinin-M (PHA-M) for Enhanced Immune Response - Jha, Deepak Kumar; Sah, Saroj Kumar; Fathima, Mehdi (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: The main objective of this study is to develop a method for in vitro T cell proliferation from rat peripheral blood mononuclear cells. Materials and Methods: The study involved female adult Albino Wistar rats, acclimatized for a week and used mononuclear cells for T cell enrichment. The cells were cultured in 24 and 6-Well Plates (WP) in the presence of PHA-M and analyzed for cytokines, cell counts, DNA content and morphology characteristics. Key Facts: MNCs were isolated and quantified, which revealed moderate to high variability across samples. The study found that TNF-α concentrations increased with the addition of PHA-M in DMEM and SFM 24-WP, with a peak at 20 µL. The 24-WP showed higher baseline and stimulated TNF-α levels compared to the 6-WP. The addition of PHA-M to DMEM 24-WP increases IFN-γ concentration, particularly at 10 µL, while it slightly decreases at 20 µL. In SFM 24-WP, it increases significantly at 20 µL. DMEM 24 WP 10 µL PHA-M has lower IL-6 concentrations, while DMEM 24 WP 20 µL PHA-M has the highest concentration. SFM 24 WP 20 µL PHA-M has significantly higher IL-6 levels. PHA-M stimulation significantly increased DNA concentration in DMEM 24 WP, with the highest concentration at 10 µL. PHA-M stimulation increased cell count, particularly with 10 µL, indicating successful proliferation. However, average cell size decreased with 10 µL of PHA-M for both media types. Conclusion: DMEM 24-WP at 10 µL of PHA-M offers a promising setup for experiments due to its balance between cytokine production and effective proliferation.
Keywords: Cell count; Cytokine; DNA; Immune Response; Mononuclear cells; Proliferation; T-cells